Analysis of The Influence of The Board of Commissioners, Directors, Audit Committee and External Audit Effectiveness On The Level of Mandatory and Voluntary Disclosure - Jason Effendi; Sylvia Veronica Siregar (The Indonesian Journal of Accounting Research, 2015)
Abstract: This study aims to examine the effect of the effectiveness of the board of commissioners, directors, audit committees and external audit (audit costs, the size of the Public Accounting Firm and the audit opinion) on the level of mandatory and voluntary disclosure. The study uses a sample of 142 non-financial public companies listed on the Indonesia Stock Exchange in 2011 and 2012. The result of the study concludes that the size of the public accounting firm has a significant negative effect on the level of mandatory disclosure, while the effectiveness of the board of commissioners and directors positively influence mandatory disclosure. The effectiveness of the directors and audit committee also positively influence the level of voluntary disclosure, whereas external audit does not influence the level of voluntary disclosure.Abstrak: Penelitian ini bertujuan untuk menguji pengaruh efektivitas dewan komisaris, direksi, komite audit dan audit eksternal (biaya audit, ukuran Kantor Akuntan Publik dan opini audit) pada tingkat pengungkapan wajib dan sukarela. Penelitian ini menggunakan sampel dari 142 perusahaan publik non-keuangan yang terdaftar di Bursa Efek Indonesia pada tahun 2011 dan 2012. Hasil penelitian menyimpulkan bahwa ukuran kantor akuntan publik memiliki pengaruh negatif yang signifikan terhadap tingkat pengungkapan wajib, sementara efektivitas dewan komisaris dan direksi berpengaruh positif terhadap pengungkapan wajib. Efektivitas direksi dan komite audit juga secara positif mempengaruhi tingkat pengungkapan sukarela, sedangkan audit eksternal tidak mempengaruhi tingkat pengungkapan sukarela.